Antiparasitic potential of chromatographic fractions of nephrolepis biserrata and liquid chromatography-quadrupole time-of-flight-mass spectrometry analysis - Muhammad Dawood Shah; Kazuki Tani; Yoong, Soon Yong; Fui, Fui Ching; Shaleh, S.R.M.; Vairappan, C.S.; Venmathi Maran (Molecular Diversity Preservation International, 2021)
Marine aquaculture development is recently impeded by parasitic leech Zeylanicobdella arugamensis (Hirudinea, Piscicolidae) in Sabah, Malaysia. The parasitic leech infests a variety of cultured fishes in aquaculture facilities. In this study, we evaluated the antiparasitic activity of the chromatographic fractions of the medicinal plant Nephrolepis biserrata methanol extract against Z. arugamensis and highlighted the potential metabolites responsible for the antiparasitic properties through liquid chromatography (LC)–quadrupole time-of-flight (QTOF)–mass spectrometry (MS) analysis. Out of seven fractions obtained through flash column chromatography techniques, three fractions demonstrated antiparasitic properties. Significant parasitic mortality was indicated by fraction 3 at a concentration of 2.50 mg/mL, all the leeches were killed in a time limit of 1.92 ± 0.59 min. followed by fraction 4 (14 mg/mL) in 34.57 ± 3.39 and fraction 5 (15.3 mg/mL) in 36.82 ± 4.53 min. LC-QTOF-MS analysis indicated the presence of secondary metabolites including phytosphingosine (6), pyrethrosin (1), haplophytine (9), ivalin (2), warburganal (3), isodomedin (4) and pheophorbide a (16), representing sphingoid, alkaloid, terpenoid, phenolic and flavonoid groups. Thus, our study indicated that the chromatographic fractions of N. biserrata demonstrated significant antiparasitic activity against the marine parasitic leeches due to the presence of potent antiparasitic bioactive compounds.